Duplex collecting system with renal malrotation: an unusual combination - Secodiningrat, Raden H. P. S.; Singgih, Nicholas A.; Oktaviani, Jacinda R.; Manuputty, Egi E. (International Surgery Journal, 2023)
Both duplex collecting system and renal malrotation are congenital developmental anomalies of kidney. They usually present asymptomatic and accidentally diagnosed while patients undergo radiology examinations. We are reporting a case of a 33-year-old-male with a combination of duplex and malrotation kidney. Although these two are common anomalies of kidney, their combination is extremely rare. We found only two reports that had similar combined cases, so our case is the third reported.